Selection of side groups on simple non‐fullerene acceptors for the application in organic solar cells: From flexible to rigid. Issue 15 (28th February 2022) - Ye, Shounuan; Chen, Shuaishuai; Zheng, Xiangjun; Li, Shuixing; Pan, Youwen; Chen, Yiyao; Fang, Jin; Ma, Changqi; Wang, Dan; Zhang, Qisheng; Shi, Minmin; Chen, Hongzheng
Abstract: The side chains on non‐fullerene acceptors (NFAs) can affect greatly the photovoltaic performances of the resulting organic solar cells (OSCs) by regulating the molecular packing and orientation of NFAs. To explore suitable side groups for asymmetric simple NFAs, in this work, we design and synthesize two A‐D1 ‐A′‐D2 ‐A type NFAs, NTC‐4Cl, and PhNTC‐4Cl, which own flexible alkyloxy and rigid aryloxy side chains on the A′ cores, respectively. Due to the same molecular backbone (A′: benzotriazole; D1 : thiophene; D2 : cyclopentadithiophene; A: dichlorodicyanoindanone), NTC‐4Cl and PhNTC‐4Cl have similar absorptions and energy levels. However, the PhNTC‐4Cl‐based OSC gives a higher power conversion efficiency than that of the NTC‐4Cl‐based one (11.09% vs. 10.82%) because PhNTC‐4Cl shows more compact π–π stacking and dominant face‐on orientation, enhancing charge transport and mitigating charge recombination. Therefore, this work provides a new insight into the molecular design of high‐performance NFAs, especially the rational choice of side groups on asymmetric simple NFAs. Abstract :